Partial substitution of wheat flour with orange sweet potato flour (Ipomoea batatas) and its effect on the bromatological and sensory properties of sweet cookies - Alcívar, Gema; Loor, Gilda; Muñoz, José (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
The objective of the research was to evaluate the partial substitution of wheat flour with orange sweet potato flour (Ospf) in the preparation of sweet cookies. A completely randomized design with a factorial arrangement was applied. The factor under study corresponded to the concentrations of Ospf (10, 20, and 30 %) plus a control treatment. Bromatological parameters, texture, and sensory profile were evaluated. The LSD Fisher and Kruskal Wallis multiple comparison tests were used at 5 % significance. The proximate composition of the orange sweet potato flour presented in protein 3.99 ± 0.02 %; moisture 8.65 ± 0.00 %; dry matter 91.34 ± 0.06 %; ash 4.24 ± 0.00 %; pH 6.41 ± 0.01; acidity 0.69 ± 0.01 % and particle size 354 ± 0.02 µm. In the processed products (sweet cookies), except for the energy parameter, the other bromatological variables presented statistical significance (p<0.05). Regarding the texture profile, the parameters hardness, brittleness, and adhesive force were significantly different (p<0.05) between the treatments, while, for adhesiveness, cohesiveness, gumminess, elasticity, and chewiness a p>0.05 (no significant) was obtained. At the sensory level, the untrained tasters expressed the acceptability of ‘‘I neither like it nor dislike it’’ in the attributes, flavor, smell, texture, and consistency; however, in color, the formulations with the factor under study presented greater acceptance. The sweet cookies met the requirements established in the INEN 2085 reference standard for cookies.